Intermittences : Memory, Justice, and the Poetics of the Visible in Uruguay - Forcinito, Ana (Book collections on Project MUSE., 2018)
"The construction of memory entails a battle not only between memory and forgetting but also between different memories. There are multiple constructions of memory, and in the dispute between them, some become hegemonic, while others remain in the margins. Ana Forcinito explores the intermittences of transitional justice and memory in post-dictatorship Uruguay. The processes of building memory and transitional justice are repetitive but inconstant. They are contested by both internal and external forces and shaped by tensions between oblivion and silence. Forcinito explores models of reconciliation to present an alternative narrative of the past and to expose the blind spots of memory"--